Asymmetry of the Modern Conflicts - Bulatova, Olena; Reznikova, Nataliia; Sarbash, Serhii (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2024)
The system of the modern global security space is characterized by an increase in insta bility, and the proliferation of local and military conflicts, which are becoming increasingly intense and protracted, thus necessitating the study of current trends occurring in the security system at the global, regional, and national levels. The objective of the article is to define the essence of asymmetry in modern conflicts to substantiate current trends in the international security environment in the context of russian war against Ukraine. It has been determined that modern conflicts exhibit asymmetric characteristics, which are determined by the political-legal and economic environment. The absence of opportunities to exercise civil and political rights, protection of freedoms, and beliefs, and a fair judicial system become sources of social tension and conflicts in society. Authoritarian countries fail to ensure the effective functioning of state institutions, and respect for civil rights and freedoms, which exacerbates institutional and social instability. The absence of conflicts is a normal state for democracies. Differences in economic potential among countries determine the possibilities for increasing military potential. It is argued that a high level of military spending does not guarantee a high level of stability in a country, and social and economic inequality further exacerbates stratification and tension in society. Countries with high levels of prosperity demonstrate the highest levels of peacefulness, which do not necessarily coincide with high levels of mili tary financing. It has been identified that the consequences of modern conflicts also have an asymmetric nature, which enhances the tendency towards the internationalization of internal conflicts: the countries most affected are those where the most intense conflicts take place, as well as their neighbouring countries. russia’s war against Ukraine has heightened the global level of danger in terms of tension and conflicts. System współczesnego globalnego bezpieczeństwa charakteryzuje się wzrostem niesta bilności, rozprzestrzenianiem się konfliktów lokalnych i wojskowych, które stają się coraz bardziej intensywne i trwałe, co wymaga zbadania współczesnych tendencji zachodzących w systemie bezpieczeństwa na poziomie globalnym, regionalnym i krajowym. Celem artykułu jest zbadanie przyczyn związku między gospodarką a konfliktem w kontekście globalizacji, określenie istoty asymetrii współczesnych konfliktów oraz uzasadnienie bieżących tendencji w międzynarodowym środowisku bezpieczeństwa w kontekście wojny Rosji przeciwko Ukrainie. Określono, że współczesne konflikty mają asymetryczny charakter, który wynika z polityczno-prawnego i ekonomicznego otoczenia. Brak możliwości realizacji praw obywatelskich i politycznych, ochrony wolności, wyznań religijnych, sprawiedliwego systemu sądowego staje się źródłem napięć społecznych i konfliktów w społeczeństwie. Autorytarne państwa nie zapewniają skutecznego funkcjonowania instytucji państwowych, szacunku dla praw i wolności obywatelskich, co pogłębia instytucjonalną i społeczną niestabilność. Brak konfliktów jest normalnym stanem dla demokracji. Różnice w potencjale gospodarczym państw określają możliwości wzrostu potencjału militarystycznego. Uzasadniono, że wysoki poziom wydatków na cele wojskowe nie gwarantuje wysokiego poziomu stabilności w kraju, a społeczna i ekonomiczna nierówność pogłębia dalszą stratyfikację i napięcia społeczne. Najwyższy poziom pokoju demonstrują kraje o wysokim poziomie dobrobytu, który niekoniecznie pokrywa się z wysokim poziomem wydatków na cele wojskowe. Określono, że skutki współczesnych konfliktów mają również asymetryczny charakter, co pogłębia tendencję do internacjonalizacji konfliktów wewnętrznych: największe straty ponoszą dotknięte nimi kraje, gdzie mają miejsce najbardziej intensywne konflikty, a także ich sąsiedzi. Wojna Rosji przeciwko Ukrainie zaostrzyła globalny poziom zagrożenia z punktu widzenia napięcia i konfliktów.
Asymetria współczesnych konfliktów
Keywords: conflict; threats; national security; global security; asymmetry; military spending; konflikt; zagrożenia; bezpieczeństwo narodowe; bezpieczeństwo globalne; asymetria; wydatki na cele wojskowe